Natural Killer T Cells and Mucosal-Associated Invariant T Cells in Lung Infections - Trottein, François; Paget, Christophe (Frontiers in Immunology, 2018)
Immune system has been traditionally divided into two arms called innate and adaptive immunity. Typically, innate immunity refers to rapid defence mechanisms that set in motion within minutes to hours following an insult. Conversely, the adaptive immune response emerges after several days and relies on the innate immune response for its initiation and subsequent outcome. However, the recent discovery of immune cells displaying merged properties indicates that this distinction is not mutually exclusive. These populations that span the innate-adaptive border of immunity comprise, among others, CD1d-restricted Natural Killer T cells and MR1-restricted mucosal-associated invariant T cells. These cells have the unique ability to swiftly activate in response to non-peptidic antigens through their T cell receptor and to modulate many aspects of the immune response. Despite they recirculate all through the body via the bloodstream, these cells mainly establish residency at barrier sites including lungs. Here, we discuss the current knowledge into the biology of these cells during lung (viral and bacterial) infections including activation mechanisms and functions. We also discuss future strategies targeting these cell types to optimize immune responses against respiratory pathogens.